Study of efficacy of compression suture in the surgical management of atonic PPH - Gadappa, Shrinivas N.; Gavit, Yogita B.; Sharma, Deepika; Mahajan, Rasika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Study was conducted to analysis efficacy of compression suture in the surgical management of Atonic PPH. It’s prospectively carried out with 60 cases required compression suture in managing Atonic PPH. Atonic uterus is preventable cause of maternal mortality and morbidity constituting 80% PPH cases. Methods: Prospective study carried out at tertiary care center for studying efficacy of compression suture in the surgical management of atonic PPH for one year, started after approval from ethical committee. Results: Compression suture is effective in managing atonic PPH. out of 60 cases, 4 patient’s required obstetric hysterectomy as a last resort to control Atonic PPH. Uterus was conserved in 93.3% of cases. Conclusions: Development of compression suture technique has proved to be effective in the control of massive Atonic PPH not responding to medical management is an alternative to hysterectomy when timely applied. It proves to be valuable addition for surgical treatment of PPH and for saving uteri after medical management of PPH failed. Authors can adopt compression suture as a mid-step before resorting to uterine devascularisation or hysterectomy when medical line of management fails. Resident doctors in teaching institutes must be well trained in this technique.